A non‐sense MCM9 mutation in a familial case of primary ovarian insufficiency. Issue 5 (10th February 2016) - Fauchereau, F.; Shalev, S.; Chervinsky, E.; Beck‐Fruchter, R.; Legois, B.; Fellous, M.; Caburet, S.; Veitia, R.A.
Abstract : Primary ovarian insufficiency (POI) results in an early loss of ovarian function, and remains idiopathic in about 80% of cases. Here, we have performed a complete genetic study of a consanguineous family with two POI cases. Linkage analysis and homozygosity mapping identified 12 homozygous regions with linkage, totalling 84 Mb. Whole‐exome sequencing of the two patients and a non‐affected sister allowed us to detect a homozygous causal variant in the MCM9 gene. The variant c.1483G>T [p.E495*], confirmed using Sanger sequencing, introduced a premature stop codon in coding exon 8 and is expected to lead to the loss of a functional protein. MCM9 belongs to a complex required for DNA repair by homologous recombination, and its impairment in mouse is known to induce meiotic recombination defects and oocyte degeneration. A previous study recently described two consanguineous families in which homozygous mutations of MCM9 were responsible for POI and short stature. Interestingly, the affected sisters in the family described here had a normal height. Altogether, our results provide the confirmation of the implication of MCM9 variants in POI and expand their phenotypic spectrum. Abstract :